Congenital familial myasthenic syndromes: disease and course in an affected dizygotic twin pair - Pavone, Piero (BMJ Publishing Group, 2013)
The present report describes clinical variability in an affected dizygotic twin pair. Twin 1 showed classical features of the congenital myasthenic syndromes (CMS), that is, ptosis, dysphonia, asthenia and hypotonia. In twin 2, these clinical signs were less pronounced, but subtle resulting in severe lumbar hyperlordosis. Molecular analysis, performed for both twins, revealed the presence of three polymorphisms in the heterozygous form in RAPSN gene. The present report highlights the clinical variability of the CMS.